The Impact of the Greening of the Supplier on Competitive Advantage: Does Green Innovation Matter in Thai Auto Industry? - Sudawan Somjai; Saroge Vasuvanich; Khomsan Laosillapacharoen; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
The main focus of the currents study is to examine the role of the greening of the supplier in achieving competitive advantages. In addition to that the study has examined the mediating role green innovation namely product innovation, process innovation, and the managerial innovation in the relationship between greening the supplier and the competitive advantage of firms in the plastic industry of Thailand. The study has used the SEM-PLS to analyses the data. Due to the number of reasons the current study is using Structural Equation Modelling (SEM). SEM assumes that variables assed without any errors and have equal capability of consideration with linear and multiple regression analysis. Although SEM is very effective for the estimation of instrument with many distinct equations of multiple regression and also involve in factor analysis and multiple regression. The results of current study show that with the encouragement of green suppliers lead towards internal green product, managerial innovation and process [1]. which will increase competitive advantage. So, this study suggest that companies should integrate their upstream and downstream suppliers for achievement of environmental goals and relive of pressure from buyers. In international market these organizations can create a lot of job opportunities as compare to their competitors. By practice organizations must dedicate considerable efforts for providing guidance, assistance and technical support to suppliers for the implementation of environmental management systems, and organizing the seminars related to environmental awareness and training sessions for helping suppliers for improvement of firm.